1997
DOI: 10.1111/j.1440-1681.1997.tb02126.x
|View full text |Cite
|
Sign up to set email alerts
|

Supramedullary Modulation of Sympathetic Vasomotor Function

Abstract: 1. Supramedullary structures including the ventral medial prefrontal cortex (MPFC) and the midbrain cuneiform nucleus (CnF) project directly and indirectly to premotor sympatho-excitatory neurons of the rostral ventrolateral medulla (RVLM) that are critically involved in the generation of sympathetic vasomotor tone. 2. Electrophysiological studies have demonstrated that activation of depressor sites within the MPFC is associated with splanchnic sympathetic vasomotor inhibition and inhibition of the activity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 74 publications
2
25
0
2
Order By: Relevance
“…This is because decerebration could have removed supramedullary excitatory and inhibitory descending controls for sympathetic outflow. In this regard, previous studies have shown that both the ventrolateral periaqueductal gray and ventral medial prefrontal cortex are important descending inhibitory pathways that modulate the RVLM neurons and sympathetic vasomotor drive (2,11,32). Data from the present study strongly suggest that the PVN autonomic neurons not only play an important role in the maintenance of basal sympathetic tone but also are required for increased sympathetic drive in response to stimulation of cardiac afferent nerves.…”
Section: Discussionsupporting
confidence: 47%
“…This is because decerebration could have removed supramedullary excitatory and inhibitory descending controls for sympathetic outflow. In this regard, previous studies have shown that both the ventrolateral periaqueductal gray and ventral medial prefrontal cortex are important descending inhibitory pathways that modulate the RVLM neurons and sympathetic vasomotor drive (2,11,32). Data from the present study strongly suggest that the PVN autonomic neurons not only play an important role in the maintenance of basal sympathetic tone but also are required for increased sympathetic drive in response to stimulation of cardiac afferent nerves.…”
Section: Discussionsupporting
confidence: 47%
“…Since that time, considerable clinical (Critchley et al, 2003;Macey et al, 2008;Norris et al, 1978;Norton et al, 2013;Oppenheimer et al, 1991;Soros and Hachinski, 2012;Woo et al, 2003), and experimental work in rodents (Cechetto and Saper, 1990) outlined the functional cardiovascular outcomes due to stimulation of, or damage to, the insula, thalamus, hypothalamus, amygdala, and medial prefrontal regions. Benarroch (1993) outlined the "central autonomic network" as a group of brainstem and supramedullary regions suspected of being associated with modulation over the autonomic nervous system, although with less emphasis on forebrain or parietal regions than provided by others Cechetto, 1995a,1995b;Cechetto and Chen, 1995;Oppenheimer et al, 1991;Verberne et al, 1987Verberne et al, , 1988Verberne et al, , 1997.…”
Section: Section 1: Overviewmentioning
confidence: 97%
“…The nerve signals then propagate to the cardiovascular control center in the brainstem for baroreflex regulation of blood pressure (Levy MN, 2007). In addition, supra-medullary structures, including midbrain cuneiform nucleus and ventral medial prefrontal cortex, also have an inhibitory role in baroreflex regulation (Verberne et al, 1997). …”
Section: Introductionmentioning
confidence: 99%